Differential Expression Profiles of mRNA and Noncoding RNA and Analysis of Competitive Endogenous RNA Regulatory Networks in Nonalcoholic Steatohepatitis - Mengjia Gao; Jingxin Xin; Xiaoling Li; Ling Gao; Shanshan Shao; Meng Zhao (Gastroenterology Research and Practice)
Nonalcoholic steatohepatitis (NASH) is a liver disease caused by multiple factors, and there is no approved pharmacotherapy. The pathogenesis of NASH remains underexplored. In this study, differentially expressed circular RNAs (circRNAs) were obtained by analyzing NASH-related circRNA datasets, and then, corresponding target microRNAs (miRNAs) and messenger RNAs (mRNAs) were predicted to construct a circRNA–miRNA–mRNA regulatory network. On this basis, a total of 38 circRNAs, 7 miRNAs, and 10 mRNAs were screened out. The present study reveals novel circRNA biomarkers of NASH and reports a potential competing endogenous RNA (ceRNA) regulatory network that might provide insights for further investigation into the underlying pathogenesis of NASH.